2009
DOI: 10.1111/j.1526-4610.2008.01324.x
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Idiopathic Intracranial Hypertension With and Without Papilledema

Abstract: Objective To compare clinical features, visual characteristics, and treatment of idiopathic intracranial hypertension patients with and without papilledema. Background Idiopathic intracranial hypertension does not often occur without papilledema. This study estimates the prevalence and compares the clinical characteristics of idiopathic intracranial hypertension patients with and without papilledema. Methods We performed a cross-sectional analysis of all idiopathic intracranial hypertension patients diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
127
0
9

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(140 citation statements)
references
References 50 publications
4
127
0
9
Order By: Relevance
“…Many studies showed a strong association between the amount of papilledema and severity of visual loss in patients with newly diagnosed IIH [7]. However, information provided by SD-OCT may diverge from analysis of visual function; compared to SAP, that is a sensitive test for visual loss, SD-OCT abnormalities can reveal early optic nerve damage also in cases without papilledema or visual field loss or when papilledema is not reversed.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies showed a strong association between the amount of papilledema and severity of visual loss in patients with newly diagnosed IIH [7]. However, information provided by SD-OCT may diverge from analysis of visual function; compared to SAP, that is a sensitive test for visual loss, SD-OCT abnormalities can reveal early optic nerve damage also in cases without papilledema or visual field loss or when papilledema is not reversed.…”
Section: Resultsmentioning
confidence: 99%
“…It is therefore natural that those who are primarily concerned in the conservation of the patient's sight should demand early or immediate operation, for it is only by operation that permanent relief of pressure can be obtained." 3 Papilledema has gained increasing interest in recent years among neuro-ophthalmologists as the result of several clinical studies demonstrating that it may have not only diagnostic potential as a measure of increased ICP [4][5][6][7] but also therapeutic potential as a measure of disease severity and response to treatment. 8 In attempting to detect and diagnose papilledema as early as possible in patients, MR imaging is becoming a useful noninvasive method.…”
mentioning
confidence: 99%
“…11 However, it seems that in any patients with chronic migraine headache that is refractory and do not respond to usual prophylactic migraine headache, it is essential that done spinal tap for rule out of idiopathic intracranial hypertension without papilledema. 12 In our study obesity was frequent in IIH patients with and without migraine, the relation between obesity and IIH remains unclear. It is seem that Healthy overweight individuals may have CSF pressure above the normal range and also the obesity associated with increased severity and frequency of migraine attacks.…”
Section: Discussionmentioning
confidence: 97%